2015
DOI: 10.18298/ijlet.483
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Learning Capacity of Efl Student Teachers

Abstract: This article examines the impact of some personal factors on the autonomous learning capacity of student teachers in a foreign language department. The sample group of the study consisted of 146 prospective English teachers in the Educational Faculty of a state university. The participants were asked to anonymously fill out a questionnaire involving two parts which respectively investigated their background and autonomous learning capacity. The first part of the questionnaire is a combination of open-ended and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…As a result, learners seem to show difficulty in breaking out of the institutionalized learning patterns, even in autonomous learning contexts as early adults. This aspect was also acknowledged by Genç (2015) who investigated the influence of personal factors towards the autonomous learning capacity of students and teachers in foreign language majors. He found that patent curriculum design has somehow 'crippled' students' opportunity and ability to modify and rearrange it.…”
Section: Statements Meanmentioning
confidence: 90%
“…As a result, learners seem to show difficulty in breaking out of the institutionalized learning patterns, even in autonomous learning contexts as early adults. This aspect was also acknowledged by Genç (2015) who investigated the influence of personal factors towards the autonomous learning capacity of students and teachers in foreign language majors. He found that patent curriculum design has somehow 'crippled' students' opportunity and ability to modify and rearrange it.…”
Section: Statements Meanmentioning
confidence: 90%
“…Dafei (2007) adds that learners can be defined as autonomous if they are responsible with the five aforementioned aspects proposed by Holec. According to Genc (2015), these five aspects are interrelated to four co-occuring behavioral syndrome factors namely (a) desire, (b) resourcefulness, (c) initiative, and (d) persistence.…”
Section: The Concept Of Learning Autonomymentioning
confidence: 99%
“…According to Ponton & Rhea (2006) resourcefulness is considered as an active approach fostered by desire to seek for more knowledge and solution. Genc (2015) adds that the autonomous learner will actively search for resources that are useful for him or her in the learning experience. Moreover, resourcefulness measures the degree to which a learner anticipates the benefits of learning, whether to prioritize learning over non-learning activities, and solving problems encountered that interfere learning desire (Ponton, 2018).…”
Section: The Concept Of Learning Autonomymentioning
confidence: 99%
“…There were 26 statements. The statements were composed based on autonomy learning activity, such as students capability in understanding learning objective, preparing personal study plan, implementing learning strategy, monitoring learning strategy, and evaluating learning activities (Genç, 2015). The questionnaire was distributed to the students via online through Google form.…”
Section: Introductionmentioning
confidence: 99%